2020
DOI: 10.1002/mnfr.202000632
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Resveratrol, Caffeine, β‐Carotene, and Epigallocatechin Gallate (EGCG) on Amyloid‐β25--35 Aggregation in Synthetic Brain Membranes

Abstract: Scope: Alzheimer's disease is a neurodegenerative condition marked by the formation and aggregation of amyloid-(A) peptides. There exists, to this day, no cure or effective prevention for the disease; however, there is evidence that a healthy diet and certain food products can slow down first occurrence and progression. To investigate if food ingredients can interact with peptide aggregates, synthetic membranes that contained aggregates consisting of cross-sheets of the membrane active fragment A 25-35 are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 91 publications
(159 reference statements)
1
10
0
Order By: Relevance
“…Moreover, using X-ray diffraction they found that caffeine leads to membrane thickening and to a decrease in membrane fluidity and in presence of the Aβ 25-35 peptides an increase in local membrane curvature was reported, which is likely induced by the formation of extracellular Aβ aggregates and fibrils. Additionally, they found in their UV-visible spectroscopy studies using thioflavin T, a significant increase in the fluorescent signal of β-sheets at 420 nm after addition of caffeine [33]. Similar results regarding the influence of caffeine on membranes were obtained in one of the authors' earlier studies [34].…”
Section: Animal Studies/molecular Pathwayssupporting
confidence: 72%
See 1 more Smart Citation
“…Moreover, using X-ray diffraction they found that caffeine leads to membrane thickening and to a decrease in membrane fluidity and in presence of the Aβ 25-35 peptides an increase in local membrane curvature was reported, which is likely induced by the formation of extracellular Aβ aggregates and fibrils. Additionally, they found in their UV-visible spectroscopy studies using thioflavin T, a significant increase in the fluorescent signal of β-sheets at 420 nm after addition of caffeine [33]. Similar results regarding the influence of caffeine on membranes were obtained in one of the authors' earlier studies [34].…”
Section: Animal Studies/molecular Pathwayssupporting
confidence: 72%
“…Gastaldo and colleagues examined in their study if food ingredients (among others caffeine) are able to affect Aβ peptide aggregation in AD through an indirect, membrane-mediated pathway, since membranes are known to play a crucial role in early stages of peptide aggregation. The authors used synthetic brain membranes to analyze the influence of caffeine on size and volume fraction of aggregates consisting of cross-β sheets of the membrane active fragment Aβ [25][26][27][28][29][30][31][32][33][34][35] . Caffeine was reported to spontaneously partition into the membranes in the first 150 ns of the molecular dynamics simulation and found to mainly position in the head-tail interface of the membranes-and some also temporarily inside the hydrophobic core.…”
Section: Animal Studies/molecular Pathwaysmentioning
confidence: 99%
“…These changes in Aβ production and degradation caused by specific lipids strongly affect the total level of Aβ peptides that aggregate in senile plaques of AD patients, one important pathological hallmark of the disease [41]. Recently, we and others have found that MTXs, that are frequently consumed in almost every area of the world, decrease Aβ generation and Aβ aggregation [13,42], and MTXs have been reported to display health benefits in many neurodegenerative diseases involving cell death in the nervous system [12]. Therefore, we analyzed in our present study whether MTXs also exert potential beneficial effects on lipids found to be changed in AD.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological relevance in terms of AD of both curcumin and homotaurine is strongly limited by their bioavailability in the human brain, which is limited by their ability to cross the blood–brain barrier. However, both molecules seem to successfully inhibit the earliest stages of amyloid peptide aggregation, i.e., the formation of nanometer sized aggregates in membranes, which form the nuclei and building blocks of larger aggregates and potentially extracellular fibers later on . As such, they can potentially interrupt the cascade of events that leads to large aggregates of amyloid and τ proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A second group of molecules are nonpeptic small-molecule antiaggregants, which interact with membranes and change membrane properties. The list of those molecules includes common drugs and food additives, such as β-carotene, resveratrol, aspirin, green tea extract, curcumin, melatonin, cholesterol, nicotine, and vitamin E. ,, Evidence was presented that curcumin, for instance, can change size and volume fraction of Aβ clusters by decreasing the hydrophobic mismatch between lipid and peptide domains in membranes . In this paper, we compare the efficacy of homotaurine, a representative of the peptidic aggregation inhibitors, and curcumin, representing a nonpeptic small-molecule antiaggregant, to inhibit Aβ 25–35 aggregation in model brain membranes.…”
Section: Introductionmentioning
confidence: 99%